1986
DOI: 10.1017/s0022029900024699
|View full text |Cite
|
Sign up to set email alerts
|

Effects of iodate, hydrogen peroxide and dichromate on the denaturation of whey proteins in heated milk

Abstract: The effect of heating raw milk at 75 °C for 30 min and at 95 °C for 15 s in the presence of varying concentrations of three oxidizing agents on the denaturation of total and individual whey proteins was measured. At 75 °C, a-lactalbumin could be protected against denaturation by both iodate and H 2 O 2 and /Mactoglobulins A and B by H 2 O 2 and dichromate. However, at concentrations above ~ 15 mM, the oxidizing agents tended to increase denaturation. At 95 °C, where the extent of whey protein denaturation was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1988
1988
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Potassium iodate had no significant effect on bovine serum albumin (BSA) denaturation at pH 6.6 (Table 1) and no detectable thermal activity of its own in the temperature range 20-120°C. This confirms the results of Marshall (1986), who used gel electrophoresis to study the heating of raw milk in the presence of potassium iodate and concluded (1) that iodate addition increased 6-lactoglobulin denaturation at both 75°C and 95"C, and (2) that BSA denaturation was unaffected by addition of potassium iodate at either 75°C or 95°C. Both BSA and (3-lactoglobulin contain disulphide bridges and sulphydryl groups.…”
Section: Disulphide Bonding In Plactoglobulin Denaturation and Aggregsupporting
confidence: 87%
“…Potassium iodate had no significant effect on bovine serum albumin (BSA) denaturation at pH 6.6 (Table 1) and no detectable thermal activity of its own in the temperature range 20-120°C. This confirms the results of Marshall (1986), who used gel electrophoresis to study the heating of raw milk in the presence of potassium iodate and concluded (1) that iodate addition increased 6-lactoglobulin denaturation at both 75°C and 95"C, and (2) that BSA denaturation was unaffected by addition of potassium iodate at either 75°C or 95°C. Both BSA and (3-lactoglobulin contain disulphide bridges and sulphydryl groups.…”
Section: Disulphide Bonding In Plactoglobulin Denaturation and Aggregsupporting
confidence: 87%
“…Several early investigations have shown that, as is in living tissues, ROS can cause food proteins to polymerize, degrade, and interact with other food components to produce complexes [ 5 , 6 , 7 , 8 ]. Subsequent research, including recent studies, has produced ample new evidence that ROS-induced physicochemical modifications could significantly alter the functionality (i.e., gelation, emulsification, foaming, film formation, and water-binding) of muscle [ 9 , 10 , 11 , 12 , 13 , 14 , 15 ], egg [ 16 , 17 ], dairy [ 18 , 19 , 20 , 21 ], legume [ 22 , 23 , 24 , 25 ], and cereal [ 26 , 27 , 28 ] proteins. Table 1 lists the proteins from different commodity food groups that have been widely subjected to oxidative studies.…”
Section: Introductionmentioning
confidence: 99%
“…For example, mild oxidation by H202 was found to facilitate egg white protein coagulation, thereby improving foaming and gelling properties (Snider and Cotterill 1972). Conversely, limited oxidation of heated milk by H202 was reported to protect whey proteins from denaturation and aggregation, and therefore, considered a suitable additive in rmlk pasteurization (Marshall 1986). However, most meat science literature has shown that under oxidative conditions, muscle proteins exhibit deteriorations in functional properties, including solubility, gel-forming ability, water-binding capacity, and viscosity (Jarenback and Liljemark 1975;Smith 1987;Decker et al 1993;Wan el al.…”
Section: Introductionmentioning
confidence: 99%